PEMANFAATAN JERAMI NANGKA DALAM PEMBUATAN MI INSTAN - Putri Nada Sirait; Shanti Fitriani; Yelmira Zalfiatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2022)
Instant noodles are food product made from wheat flour and ripen after being cooked or brewed using boiling water or hot water in a short time. Instant noodles in this study were made using jackfruit straw. The purpose of this study was to get the selected treatment in the utilization of jackfruit straw on the characteristics of instant noodles. Treatment in the study were the use of jackfruit straw, namely JN1 (puree jackfruit straw 12.5%), JN2 (puree jackfruit straw 25%), JN3 (puree jackfruit straw 37.5%), and JN4 (puree jackfruit straw 50%). The study used a complete randomized design (CRD) with four treatments and four repeats. Data obtained was then statistically analyzed using analysis of variance (ANOVA) and then continued with Duncan’s Multiple Range (DMRT) at 5% level. The results showed that the use of jackfruit straw significantly affected moisture, ash, protein, crude fiber, elongation, cooking loss, rehydration power, and hedonic sensory test assessment of overall. JN2 treatment was chosen as the selected treatment which had 4.85% moisture, 0.77% ash, 8.82% protein, 3.87% crude fiber, 23.25% elongation, 8.50% cooking loss, 134.35% rehydration power, and hedonic assessment of overall rating is a bit liked by the panelists. Keywords:jackfruit straw, instant noodles, wheat flour